Efecto fungistático de aceites minerales parafínicos para control de sigatoka negra mycosphaerella fijiensis morelet en plantas de banano musa spp - Espinoza Ruiz, Roberto Rafael (2017)
The present research work was carried out in a experimental area located in the parish of Jesus Maria, Canton Naranjal, province of Guayas, this essay carried out in banana plants of the variety Williams of 10 weeks of age with an average height of 1.40 m. Currently, from January to July 2017, are exported 144,365,031 tons (boxes of 18.14 kg) to different destinations in the world. One of the most serious problems facing the country is the presence of black sigatoka, manifesting the damage to the leaves with severe injuries, known as pinches and striae that increases the attack of the fungus was observed necrotic spots that reduce the photosynthetic activity causing alterations in their physiology, minimizing crop productivity, deteriorate the quality of the fruit and the profitability, thus generating losses of up to 100%. In last times tests have already been realized making use of mineral oils and their results are not questionable but the effects phytotoxic were the great problem of these. Performed tests with mineral oils to high doses, but minimizaban the weight of the fruit, reduced the photosynthetic activity, but they had a greater effect fungicide in the control of the fungus, but not with a criterion to certify the mineral oils effective in its operation and that do not cause alterations in the plant. Now the possibility of using a mineral oil paraffinic and test its antifungal proprieties against the fungus of black sigatoka is done at the field level with the environmental conditions that favor the efficiency of oils and observe the behavior of the fungus in the days of their assessment. For this was determined the effect fungistatic of mineral oils paraffinic for the control of black Sigatoka (Mycosphaerella fijiensis Morelet) in banana plants (Musa spp.) using the method of Sheet simple or single leaf test. For this experimental work was conducted 7 treatments with 5 replicates including the witness, four treatments such as T1 (Spray Oel), T2 (Banole HV), T3 (Max Torque) and T4 (Harvestol) are mineral oils paraffinic to 100% and two treatments T5 (Banana Film) and T6 (Cosmo Oil) are adjuvants that acted as a replacement of the oils, the T7 (absolute control) was not applied any product. The application of the treatments was carried out in the right margin of leaf 1 and 2 by making use of a tank of CO2 and a nozzle TJ 800-05 that simulates an application commercial air getting a homogeneity of product applied on the margin of the sheet, with a dose of 500 cc (150 cc of product + Emulad 1% + Water) for mineral oils paraffinic and 500 cc (26.42 cc of product + Water) to the interveners, taking as variables the evaluation of growth of the fungus expressed in percentages each 7, 14, 21, 28, 35, 42, 49 days on leaf 1 and 2 for each treatment, the area under the disease progress curve (AUDPC) and the evaluation of phytotoxicity of mineral oils and the coadjuvants applied. For the statistical tests, conducted a one-way ANOVA and the randomized complete block design (DBCA). According to the results obtained, for the effect of protection that possess mineral oils on leaf 1 and observe the curative effect on leaf 2, the treatments T1, T2, T3 and T4 present a better control of the disease, showing equality statistics, unlike the coadjuvants did not show an effect fungisctatic for control of the fungus, while the results in the area under the curve of the progress of the disease in the week 49 T1 presents an index of 543.20 less than the other treatments in the leaf 1 and T2 presents a lower rate of 315.70 less than the other treatments in leaf 2.